First experience of using biological prosthesis "UniLine" for correction of heart valve diseases - Zhurko, S.; Olzhayev, F.; Chiginev, V.; Fedorov, S. (Personalized medicine and Global Health, 2015)
To conduct a clinical study of immediate results, assessment of hemodynamic characteristics of developed a new biological stented prosthesis «UniLine» (Russia, Kemerovo) designed for correction of heart valve lesions of various etiologies.
2 nd International conference "Personalized medicine and Global Health"
Keywords: hemodynamic characteristics; valves correction; patients